Dissecting antibody-dependent enhancement modulation by Fc-modified cross-neutralizing human monoclonal antibody - Subenya Injampa; Surachet Benjathummarak; Sujitra Keadsanti; Rochanawan Sootichote; Wilarat Puangmanee; Atsushi Yamanaka; Tadahiro Sasaki; Pongrama Ramasoota; Pannamthip Pitaksajjakul (PeerJ, 2025)
Background: Dengue is a mosquito-borne disease caused by four dengue virus serotypes (DENV1 to DENV4). Secondary infections can generate flavivirus cross-reactive antibodies at sub-neutralizing levels. This phenomenon can significantly increase the severity of secondary infections through antibody-dependent enhancement (ADE). ADE is associated with a high risk of viral infection in immune effector cells, triggering cytokine cascades and activating the complement system, which can lead to severe symptoms. Despite extensive studies, therapeutic antibodies, particularly fully human monoclonal antibodies, which could serve as candidates for immune passive therapy, have not yet been discovered. Methodology: suppression-of-enhancement assay in K562 cells. Result: ADE, indicating that they are promising candidates for future dengue treatment.
Keywords: Monoclonal and Polyclonal Antibodies Research; Mosquito-borne diseases and control; Transgenic Plants and Applications